Effect of Gamma Irradiation on the Optical Characteristics of PVA-PANI Composite Polymer Films - Othman, Norfazlinayati; Harun, Mohd Hamzah; Mohamed, Mahathir; Alias, Mohd Sofian; Talib, Zainal Abidin (Journal of Material Science and Radiation, 2025)
This manuscript reports the optical and structural characteristics of PVA/PANI composite polymer films synthesized through gamma-irradiation-induced in-situ polymerization. The in-situ formation of the conductive emeraldine salt phase of polyaniline (PANI) within the polyvinyl alcohol (PVA) binder matrix was achieved under different irradiation doses. The formation of the conductive PANI phase and the presence of Cl⁻ counter-ions were confirmed through FESEM morphological analysis and EDAX elemental mapping, respectively. XRD spectra further verify the semi-crystalline nature of the composite and indicate the structural role of PVA as a binder in stabilizing the polymeric composite system. Thermal behavior analysis using TGA reveals four distinct decomposition phases, with the most pronounced thermal transition observed in the composite irradiated at 50 kGy, suggesting enhanced structural interactions between PVA and PANI at this irradiation dose. Overall, the results demonstrate that gamma irradiation is an effective route for modifying the optical, structural, and thermal properties of PVA/PANI composites, making them promising candidates for optoelectronic and conductive polymer applications